PEER INSTRUCTION IN A HYBRID AND DIGITAL CONTEXT AS A COLLABORATIVE MEDIATION STRATEGY - Pereira Nicácio, Jailton; Trajano de Souza, Joseilson; Trajano de Souza, Josenete; Lisboa Galvão do Nascimento, Jonatha; Modesto Favacho, Kelsin; Helena de Paula Modesto Favacho, Lucia; Santos do Nascimento, Marielza; Campos Rodrigues, Mayara; Ricardo Pereira Accioly, Sérgio (Revista Gênero e Interdisciplinaridade, 2026)
The present study aims to analyze the possibilities and limits of applying Peer Instruction in the contemporary hybrid context, considering pedagogical, technological and evaluative implications. The research, of a bibliographic nature, involved a systematic survey of scientific articles, book chapters and critical essays published in specialized journals and digital repositories. This selection prioritized studies that address the integration of interactive resources, the criteria for validating knowledge produced between peers and the tensions related to student autonomy and the culture of performance. The incorporation of this collaborative approach has been consolidated as an innovative proposal capable of shifting the teaching focus and stimulating more participatory learning processes. However, implementation in digital and hybrid environments highlights contradictions between formative potential and risks of superficializing debates. Aspects such as personalized feedback, the quality of interactions and the legitimization of collectively constructed knowledge appear as challenges that demand pedagogical intentionality and clarity of objectives. The reflection presented considers that no methodology is neutral: choices about platforms, evaluation criteria and modes of engagement configure symbolic disputes and tension institutional values. The study proposes understanding teaching through peer instruction as a possibility of expanding student authorship, if it is anchored in ethical references, sensitive practices and openness to ongoing revisions.